Fold it: Recent finds of figural handles from Roman folding knives in Denmark - Søndergaard, Louise; Aarsleff, Esben; Birch, Thomas; Andreasen, Rasmus (Danish Journal of Archaeology, 2025)
A few years ago, an article on Roman folding knives in Denmark would have been unfeasible, as this small and distinct group of artifacts had not yet been identified. However, the increasing use of metal detectors in Denmark has led to the discovery of numerous new artifact types, some readily identifiable and others less so. The identification process of this new type began with the discovery of a complete folding knife in Gl. Rye cast in copper alloy. While initially proposed to be of Roman origin, this attribution was met with skepticism due to the early dating it implied, resulting in a lack of consensus among both detectorists and archaeologists. Subsequent discoveries of similar folding knife fragments have since emerged, beginning with a find from Oslo, Norway, followed by two fragments from different regions in Jutland, Denmark, as well as a fragment from a distinct handle type uncovered in Zealand, Denmark. To date, these represent the entirety of identified fragments from southern Scandinavia. This article presents and contextualizes this material. Moreover, the article argues for a Roman provincial origin of these artifacts. It examines their iconographic features and archaeological context, complemented by metallurgical analyses. ...